Design of Complementary Hexagonal Metamaterial Based HMSIW Band-Pass Filter and Reconfigurable SIW Filter Using PIN Diodes - Boubakar, H.; Abri, M.; Benaissa, M. (Advanced Electromagnetics, 2021)
This paper is divided into two sections, in the first section, a new SIW and a half-mode SIW band-pass filters based on complementary hexagonal metamaterial cells (C-HMCs) are proposed. Firstly, the SIW is analyzed in case of using two C-HMC cells and in the case of using four of these cells. Secondly, the HMSIW tunable BPF is studied and optimized. The size of the half mode is reduced by almost 50%. This filter design has a very high insertion loss about -0.4 dB, and significant transmission bandwidth extending from 5.9 GHz to 6.5 GHz. In the second section of this paper, an electronically reconfigurable SIW band-pass filter is proposed. By implementing two PIN diodes in the gaps of the two C-HMC, the results of turning the diodes ON or OFF individually is a switching in the frequency center, between 5.8 GHz and 6.8 GHz. Also, a dual band with two frequency centers at (5.6 GHz and 7.4 GHz) is achieved by turning both of the diodes ON. In addition, the metamaterial properties of all the proposed filters are investigated and presented in this work.